2022
DOI: 10.21203/rs.3.rs-1840692/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impacts of the Use of Biomass Solid Fuels for Household Cooking in Sub-Saharan Africa - A Review

Dada Oluwatosin,
Kamiyo Ola,
Adewumi Olayinka

Abstract: The establishment of weak and inefficient institutions frameworks has left many Sub-Saharan African (SSA) countries in continuous use of biomass solid fuels (BSF) which hinders economic growth and development. The literature on BSF use in SSA shows significant variation in the type of fuel preferences for domestic purposes. This study performs a critical analysis of the impact of continual usage of solid biomass fuel for cooking among households across SSA countries. The analysis was carried out via a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As presented in Figure 5, only the Euro area and sub-Saharan Africa (SSA) recorded trends beyond the world average for the period. The position for sub-Saharan Africa (SSA) is not shocking as about 40% of the population living below US$1.9 daily as of 2018 according to the World Bank ( 2020), hence a majority of the households have no option but to make use of solid fuel for cooking (Oluwatosin et al, 2022). Thus, in sub-Saharan Africa (SSA), the basic source of energy meant for cooking in rural areas and some few households in most of the cities are from solid fuels like charcoal, firewood, agricultural residues, animal dung, and household wastes.…”
Section: Self-createdmentioning
confidence: 99%
“…As presented in Figure 5, only the Euro area and sub-Saharan Africa (SSA) recorded trends beyond the world average for the period. The position for sub-Saharan Africa (SSA) is not shocking as about 40% of the population living below US$1.9 daily as of 2018 according to the World Bank ( 2020), hence a majority of the households have no option but to make use of solid fuel for cooking (Oluwatosin et al, 2022). Thus, in sub-Saharan Africa (SSA), the basic source of energy meant for cooking in rural areas and some few households in most of the cities are from solid fuels like charcoal, firewood, agricultural residues, animal dung, and household wastes.…”
Section: Self-createdmentioning
confidence: 99%
“…Even since the early 1990s, innovative epidemiological studies showed the interconnected experience of indoor air pollution from solid fuel use with public health consequences [3], developing countries still depend on solid fuel use. Especially in sub-Saharan Africa where households are left with lower options for clean fuel use than to use solid fuels for cooking [4]. The consumption of wood fuel per capita in this region is 2-3 times more likely than in any other region of the world [5].…”
Section: Introductionmentioning
confidence: 99%